Low-voltage programming of RRAM-based crossbar arrays using MOS parasitic diodes - Maheshwari, Sachin; Serb, Alex; Prodromakis, Themis (Frontiers in Nanotechnology, 2025)
Due to their high density, scalability, and low-power properties, 1-transistor-1-resistor (1T1R) RRAM-based crossbars have been exploited in the past. However, the series resistance of the transistor is a major problem in 1T1R crossbar arrays. This limits the maximum current available for inducing resistive switching and degrades the array’s performance. To mitigate this issue, we propose a new configuration—1-transistor-1-diode-1-resistor (1T1D1R)—in which diodes are used (including bulk source/drain parasitic diodes of the access transistor) to bypass the gating transistor during the programming operation (“write”). The proposed solution trades increased overhead in the layout area for a dramatic increase in the maximum achievable current drive on RRAM devices, resulting in the ability to deliver 1.5 mA+ with a voltage supply as low as 1.2 V using minimum-size devices (in our implementation). We designed a 32 × 32 crossbar array with on-chip peripheral circuitry in commercially available 0.18 μm triple-well CMOS technology for the proof of concept. We demonstrate bidirectional programming, showing a memristance change of ≈500 Ω for 120 and 80 pulses in positive and negative directions, respectively.